The girl with all the gifts [videorecording (DVD)] - Arterton, Gemma; Considine, Paddy; Marinca, Anamaria (Lionsgate, 2017)
Humanity has been all but destroyed by a fungal disease that eradicates free will and turns its victims into flesh-eating 'hungries'. Only a small group of children seem to be immune to its effects. At an army base in rural England, these unique children are being studied and subjected to cruel experiments. When the base falls, one little girl escapes and must discover what she is, ultimately deciding both her own future and that of the human race.